Age-related changes in muscle strength and spinal kyphosis angles in an elderly Japanese population - Kasukawa Y; Miyakoshi N; Hongo M; Ishikawa Y; Kudo D; Suzuki M; Mizutani T; Kimura R; Ono Y; Shimada Y (Clinical Interventions in Aging, 2017)
Yuji Kasukawa, Naohisa Miyakoshi, Michio Hongo, Yoshinori Ishikawa, Daisuke Kudo, Masazumi Suzuki, Takashi Mizutani, Ryouta Kimura, Yuichi Ono, Yoichi Shimada Department of Orthopedic Surgery, Akita University Graduate School of Medicine, Akita, Japan Abstract: Lumbar kyphosis and the decreased mobility of the lumbar spine increase the risk of falls and impair both the quality of life and the ability to perform activities of daily living. However, in the elderly Japanese population, little is known about the age-related changes and sex-related differences in muscle strength, including of the upper and lower extremities and back extensors. An adequate kyphotic or lordotic angle has also not been determined. In this study, we evaluated the age-related changes in muscle strength and spinal kyphosis in 252 males and 320 females ≥50 years of age. Grip, back extensor, hip flexor, and knee extensor strength; thoracic and lumbar kyphosis; and spinal inclination in the neutral standing position were assessed, together with the range of motion of the thoracic and lumbar spine and spinal inclination. Grip strength, back extensor strength, and the strength of the hip flexors and knee extensors decreased significantly with aging, both in males (P<0.0001) and in females (P=0.0015 to P<0.0001). The lumbar but not the thoracic kyphosis angle decreased significantly with aging, only in females (P<0.0001). Spinal inclination increased significantly with aging in both males (P=0.002) and females (P<0.0001). Back extensor strength and the thoracic kyphosis angle were significant variables influencing the lumbar kyphosis angle in both sexes. Spinal inclination correlated significantly with both the lumbar kyphosis angle and hip flexor strength in males, as well as with the lumbar kyphosis angle in females. Keywords: aging, gender, grip strength, back extensor strength, spinal curvature